Geostatistical discrimination between different sources of soil pollutants using a magneto-geochemical data set - Zawadzki, Jarosław; Szuszkiewicz, Marcin; Fabijańczyk, Piotr; Magiera, Tadeusz (Chemosphere, 2016)
The primary goal of this work was to distinguish between soil pollution from long-range and local transport of atmospheric pollutants using soil magnetometry supported by geochemical analyses. The study area was located in the Izery region of Poland (within the "Black Triangle" region, which is the nickname for one of Europe's most polluted areas, where Germany, Poland and the Czech Republic meet). One site of the study area was situated in the Forest Glade and was exposed to anthropogenic pollution from a former glasswork. The second site of the study area was located on a neighboring hill (Granicznik) of which the western, northwestern and southwestern parts of the slope were exposed to the long-range transport of atmospheric pollutants from the Czech Republic, Germany and Poland. Magnetic susceptibility was measured on the soil surface and in the soil samples using a MS2 Bartington meter equipped with MS2D and MS2C sensors, respectively. Using soil magnetometry, it was possible to discriminate between long-range transport of atmospheric pollutants and anthropogenic pollution related to the former glasswork located in the Forest Glade. Additionally, using MS2C measurements and geochemical analyses of sixteen trace elements, it was possible to discriminate between natural and anthropogenic origins of a soil magnetic susceptibility signal. Our results indicate that the Forest Glade site is characterized by relatively significant anthropogenic translocation of topsoil horizons, presence of artefacts, more hot spots, very high spatial variability, and higher nugget effect than on the Granicznik Hill.
Keywords: Soil Pollutants; magnetometrie; Česká republika; Poland; látky znečišťující vzduch; Magnetometry; Soil; Czech Republic; Environmental Monitoring; Trace Elements; Germany; látky znečišťující půdu; půda; Polsko; stopové prvky; monitorování životního prostředí; Německo; Air Pollutants